The Clinical Cost of Delays in Switching Therapy - Sharon Walmsley (Canadian Journal of Infectious Diseases and Medical Microbiology)
Management of the HIV patient with treatment experience continues to improve and evolve. New guidelines suggest that the goal of therapy should be maximal virological suppression. This is best achieved by using combinations of agents to which the virus is most likely to have some susceptibility and, where possible, by using agents within a new therapeutic class. The cases discussed demonstrate how the use of a potent regimen as salvage therapy can have good clinical, immunological and virological outcomes. However, if the salvage regimen selected is not potent enough to achieve these goals, the durability of the response is limited. The key lesson is that these strategies should be built on potency and agents should not be held back in case the strategy fails.